A Systematic Review of Households’ Fecal Sludge Management Situation to Identify Gaps and Improve Services : A Case of Kigali City, Rwanda - Murebwayire, Marie Leonce; Nilsson, Erik; Nhapi, Innocent; Wali, Umaru Garba (Sustainability (Switzerland), 2025)
Background: Kigali, Rwanda’s rapidly growing capital, faces major challenges in household-level Fecal Sludge Management (FSM), with over 89% of households using pit latrines and only 48% accessing unshared sanitation. FSM services are limited, costly, and poorly executed, leading to frequent illegal dumping. Objective: This review analyzes the literature on sanitation in Kigali to identify key gaps, synergies, and recommendations for improvement. Methods: Following PRISMA 2020 guidelines, 73 relevant publications were selected from various scientific and governmental sources. Publications were included only if they were published from 2013 to 2024 and had information on sanitation in Kigali. NOS and JBI tools were utilized to assess the quality of included publications. Results: Data were categorized into four themes, (1) access to sanitation, (2) FSM services, (3) public health, and (4) sanitation governance, and analyzed using thematic, narrative, and descriptive methods. Findings reveal a dysfunctional FSM service chain, weak policy enforcement due to overlapping responsibilities, underfunding, and limited private sector participation. These issues contribute to poor sanitation, inadequate hygiene, and prevalence of diarrheal diseases and Tropical Neglected Diseases, especially among young children. Conclusions: The review recommends strengthening governance and clarifying roles, enforcing adaptable regulations, promoting public–private partnerships, and managing the full FSM service chain more effectively. Future research should focus on developing context-specific technologies and financing strategies to support sustainable FSM solutions in Kigali.
Publisher Copyright: © 2025 by the authors.
Keywords: fecal sludge service chain; household sanitation; onsite sanitation; pit latrines; sanitation policy